Use of Triaxial Accelerometry during the Dance Aerobic Fitness Test: Considerations for Unit Positioning and Implications for Injury Risk and Performance. Issue 3 (September 2018) - Brogden, Chris Michael; Armstrong, Ross; Page, Richard; Milner, Debbie; Norris, Debbie; Greig, Matt
Injury incidence in dance is high, in large part due to the frequency of repetitive and complex movements that require the lower limb to absorb and utilize extreme forces. The aim of this study was to quantify the biomechanical demands of the Dance Aerobic Fitness Test (DAFT) via triaxial accelerometry and utilize it to compare loading at the cervical spine and distal aspect of the lower limb. University dancers (N = 26; age: 20.0 ± 1.5 years; height: 1.61 ± 0.08 m; body mass: 58.40 ± 6.20 kg) completed two trials (one familiarization and one experimental) of the DAFT, consisting of five incremental levels of dance performance. Micromechanical electrical systems (MEMS) accelerometry was used to calculate total accumulated PlayerLoad (PL Total ) and it's uniaxial (anteroposterior [PL AP ], mediolateral [PL ML ], and vertical [PL V ]) components for each level. MEMS units were positioned at cervical vertebra 7 (C7) and the center of gastrocnemius (LL). There was a significant main effect for each level, with loading increasing in relation to exercise duration. There was also a significant main effect for anatomical placement, with higher PL Total (C7 = 41.05 ± 7.31 au; LL = 132.58 ± 35.70), PL AP (C7 = 12.96 ± 2.89 au; LL = 47.16 ± 13.18 au), and PLML (C7 = 10.68 ± 2.15; LL = 46.29 ± 12.62 au) at LL when compared to C7, with the converse relationship for PL V (LL = 20.05 ± 3.41 au; C7 = 44.89 ± 11.22 au). Significant interactions were displayed for all PL metrics. It is concluded that triaxial PlayerLoad was sensitive enough to detect increased loading associated with increases in exercise intensity, while lower limb accelerometer placement detected higher loading in all planes. The specificity in anatomical placement has practical implications, with lower limb accelerometry recommended to assess movement strategies in that location.